Jangka Waktu Pengembalian Barang Elektronik Sistem Garansi Perspektif Mazhab Syafi’i Dan Undang-Undang Perlindungan Konsumen Nomor 8 Pasal 27 Huruf (E) Tahun 1999 - Zaenol Hasan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2020)
In a transaction, especially electronic goods cannot be separated from the possibility of defects or damage to goods, thus causing electronic goods manufacturers to provide guarantees (warranties) to consumers. Law Number 8 Article 27 Letter (e) of 1999 discusses consumer protection, which one of the articles is the period for demanding damaged goods is 4 years or in accordance with the contract, not exceeding the maximum period. This study aims to describe the period of return of electronic goods warranty system from the perspective of shafi'I school of thought and the period of return of electronic goods warranty system according to consumer protection law number 8 article 27 letter (e) of 1999. The research method used is a qualitative method through data techniques in the form of, observation, and documentation. The analysis technique uses the content analysis method. The results of the study concluded that: Imam Shafi'i Mazhab argues that the state of khiyar is not more than three days, it is a relief (rukshah). In transactions, especially electronic products, manufacturers use a warranty system that is in accordance with Law No. 8 Article 27 letter (e). The period to sue for defective goods is 4 years or according to the contract, not exceeding the maximum period.